2016
DOI: 10.1080/1744666x.2016.1221343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and diagnosis of epidermolysis bullosa acquisita

Abstract: Introduction: Epidermolysis bullosa acquisita (EBA) is a rare autoimmune blistering disease of skin and mucous membranes. EBA is caused by autoantibodies against type VII collagen, which is a major component of anchoring fibrils, attaching epidermis to dermis. Binding of autoantibodies to type VII collagen leads to skin fragility and, finally, blister formation. The clinical picture of EBA is polymorphic, with several distinct phenotypes being described. Despite recent progress in understanding the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 160 publications
0
100
0
17
Order By: Relevance
“…IB is a serological technique performed on extracts of tissues or cells or recombinant Col7 proteins (Fig. ) . IB is effective for diagnosing EBA by detecting autoAbs in patient sera that label the Col7 α‐chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IB is a serological technique performed on extracts of tissues or cells or recombinant Col7 proteins (Fig. ) . IB is effective for diagnosing EBA by detecting autoAbs in patient sera that label the Col7 α‐chain.…”
Section: Resultsmentioning
confidence: 99%
“…The IgG autoantibodies (autoAbs) accounting for these DEJ immune deposits were found to be autoAbs directed against a 290‐kDa protein called type VII collagen (Col7), the major component of anchoring fibrils (AFs) in the DEJ . Since these initial observations, the diagnostic testing for EBA has undergone significant refinement …”
mentioning
confidence: 99%
“…Alternative immunological tests available in specialized laboratories include immunoblotting, with the dermal extract containing the full-length 290 kDa type VII collagen protein and the recombinant NC1 domain. [3] In a recent multicenter retrospective serological study on 95 sera from EBA patients, Schmidt et al . concluded that type VII collagen combined NC1/NC2 domains ELISA is superior to ELISA based on type VII collagen NC1 domain only, immunoblotting, and IIF on salt-split skin, with a sensitivity of 97.9%.…”
Section: Indirect Immunofluorescencementioning
confidence: 99%
“…Although several tests are available for this purpose, most of which are not available in routine pathology laboratories. [3]…”
mentioning
confidence: 99%
“…Auch wir können hier nicht eindeutig beweisen, dass Kollagen Typ VII das Autoantigen darstellt, allerdings ist das "u-serrated-Muster" der direkten IF ein sehr starker Hinweis darauf. Für manche Autoren gilt diese diagnostische Methode als Goldstandard der Epidermolysis bullosa acquisita/ des bullösen SLE [30][31][32][33] Autoimmundiagnostik: ANA positiv (1:2560), gesprenkeltes Fluoreszenzmuster, SS-A/Ro-Antikörper >240 U/ml (<10 U/ml), SS-B/La-Antikörper>320 U/ ml (<10 U/ml), Komplementfaktoren im Normbereich.…”
Section: Diskussionunclassified